Geriatric mental health disaster and emergency preparedness - John A. Toner; editor; Therese M. Mierswa; associate editor; Judith L. Howe; associate editor
This book provides a comprehensive overview of the essential information that everyone working, or hoping to work in the field of aging, should know about disasters, emergencies, and their effects on the mental health and well-being of older persons. It provides the reader with evidence-based approaches for identifying and classifying mental health problems, such as Post-Traumatic Stress Disorder (PTSD), depression, and substance use disorders in older adults, which may occur during and post disasters/emergencies